The economics of business enterprise : an introduction to economic organisation and the theory of the firm - Ricketts, Martin J. (Cheltenham, UK ; Northampton, MA : Edward Elgar Pub., 2002)
To own or not to own? To make or to buy? To franchise or to manage? To contract long or to contract short? To trust or not to trust? To license or not to license? These and other organizational questions are the subject matter of this introduction to the theory of economic organization. This third edition is updated and contains a new section on the burning issue of privatization policy in the east and west, along with an exposition of the new micro-foundation of property rights theory.
Includes bibliographical references (p. 537-574) and index.
gau 21/05/14; oif 27/01/15
Loan
Keywords: Business enterpises; Corporations; Production (Economic theory); Entrepreneurship; Competition